Foliar application of manganese increases sugarcane resistance to orange rust. (9th June 2019) - Mesquita, G. L.; Tanaka, F. A. O.; Zambrosi, F. C. B.; Chapola, R.; Cursi, D.; Habermann, G.; Massola, N. S.; Ferreira, V. P.; Gaziola, S. A.; Azevedo, R. A.
Abstract : Orange rust ( Puccinia kuehnii ) is a serious disease compromising the sustainability of sugarcane ( Saccharum spp.) production. The objective of this research was to study whether supplemental manganese (Mn) supplied through foliar sprays ameliorates negative effects of orange rust on sugarcane and, if so, to reveal the underlying mechanisms. The experiment was conducted using a sugarcane variety susceptible to the disease; a single spray of Mn at 5 g L −1 (Mn0.5% ) or 10 g L −1 (Mn1% ), plus a control (Mn0% ) was performed before pathogen inoculation. Symptom severity, antioxidant metabolism, lignin deposition and anatomical organization were evaluated. Photosynthesis was also measured in newly expanded leaves and plants were harvested to estimate growth responses. The percentage diseased leaf area was reduced from 15% under Mn0% to 2.2% and 0.9% under Mn0.5% and Mn1%, respectively. This decrease was accompanied by increases in biomass production in the plants. Scanning and light microscopy images revealed that Mn treatment caused direct damage to the fungal spores and improved lignin deposition in the mesophyll. In the presence of the disease, Mn‐sprayed leaves exhibited lower levels of oxidative stress, in addition to improved structural organization of xylem and phloem vessels compared to the untreated control. The negative effects of orange rust on gas exchange and photochemistry were also ameliorated by Mn application. The results give insight into the mechanisms underlying augmented sugarcane resistance to orange rust under supplementary foliar Mn spray and contribute to the development of sustainable crop production systems by offering alternatives for reduction of disease damage.